Kemandirian BUM Desa terhadap Pertumbuhan Ekonomi Desa di BUM Desa Suwaluh Mandiri Sejahtera: Pengabdian - Mawardi, Imam (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Village economy is one of the foundations for achieving village welfare. Law Number 6 of 2014 concerning Villages explains that villages can be more independent in building and developing their respective villages. One of the instruments in village development and development is the Village-Owned Enterprise (BUM Desa) which has the flexibility to manage and utilize the potential owned by the village in order to generate profits that have an impact on the village's original income to support the independence of the village economy. The method in collecting this data is as follows: the necessary data collection techniques, both primary and secondary data and interviews, observations and FGDs by means of being carried out to obtain data directly from sources including the following sources: Management of BUM Desa Suwaluh Mandiri Sejahtera and Suwaluh village officials. The results and discussion are that the government through the Regulation of the Minister of Villages, Development of Disadvantaged Regions, and Transmigration Number 2 of 2016 concerning the Village Development Index classifies villages with the aim of facilitating village management and planning.